TEOLOGI ASY’ARIYAH: SEJARAH DAN PEMIKIRANNYA - Yogi Sulaeman; Zinul Almisri; Kerwanto (EL-ADABI : Jurnal Studi Islam, 2023)
Asy'ariyah is a theology founded by Abu Hasan Al-Asy'ari. This theology is often referred to as "Moderate Theology". He is an important figure who has a great influence nowadays. This study uses a Literature Study Methods, aiming to explain and elaborate how the history of the birth of Asy'ariyah and his thoughts, especially about Kasb and about reason and revelation. This theological formulation was utilizing textual arguments in the form of sacred texts from the Qur'an and Sunnah, such as what muhadditsin did, and also using rational arguments in the form of mantiq and logic. This approach was quite unique, he had been able to take the good things from Salafiyyah-textual approach but not as strict as Hanabilah did in their rejection of logical arguments and in the form of combination of logical-contextual approach but not as free as what Mu'tazilah did. The Asy'ariyah's theological attitude towards contemporary life is open, realistic, pragmatic, (selective, critical, and accommodating and responsive) to advances in science and technology. In sum, by looking the trajectory and how strong the foundation of Asy’ariyah paradigm is, it has been manifested in the form of Its relevance and how it maintains Ahl Al-Sunnah wa Al-Jama'ah in contemporary life.